Solvent-less Oxidation of Aromatic Alcohols Using CrO3/Al2O3 under Ultrasonic Irradiation - Maulidan Firdaus; Triana Kusumaningsih; Ichsan Arifagama; Zuhdi Alqowamul Amin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Alcohol oxidation plays an essential contribution to the chemical industry. Innovative green techniques, such as ultrasound irradiation, could be economically remarkable by enhancing reaction yield. In this research, the design and improvement of a new green ultrasound-assisted oxidation of alcohols procedure using CrO3 supported by Al2O3 with the addition of a small amount of t- butanol were reported. The oxidation of alcohols was also done without ultrasound irradiation to study the sonochemical effect. Based on FTIR and GC/MS analyses, the alcohols were effectively oxidized into their corresponding aldehydes in satisfactory yields (74–93%). The yield of the obtained aldehydes was increased by applying the ultrasonic irradiation technique, and no over-oxidation products were found. Overall, the innovative procedure offers several benefits, such as being easy to use, environmentally friendly, capable of improving yields, and having shorter oxidation times.